The impact of electronic planning management in improving the quality of nursing care in Baghdad hospitals - jasim, basima; ali, najem (Iraqi National Journal of Nursing Specialties, 2012)
Management is considered as most important resource of the society ones in modern era and an exchangepoint in societies’ lives in order to achieve its goals and wishes. So far, management behinds the newelectronic society has become different in shape and nature due to the force of the nature of informationtechnology that shapes the relationships between the world’s individuals at the national level but it goesbeyond the international ones. The study aims at identifying the impact of the electronic management’scomponents upon the improvement of the quality of nursing care in Baghdad’s hospitals. The descriptivedesign, with a sample-survey approach, is used as appropriate ones for the field study of social phenomena.So, it presents data about these phenomena and the relations between their reasons, results and analysis todepict the effective factors in them. The study uses a questionnaire for data collection from the respondents.It is comprised of (31) items which are distributed on two parts; first, demographic characteristics (8) itemsand second, electronic management’s components with a five levels Likert Scale of strongly disagree,disagree, uncertain, agree, and strongly agree with a rating scale of 1 for strongly disagree, 2 for disagree, 3for uncertain, 4 for agree, and 5 for strongly agree, respectively. Validity of the questionnaire is determinedthrough its administration to panel of (10) experts who are specialists to present their judgments about itscontent validity. Reliability of the questionnaire is determined through the use reliability coefficients toachieve its internal consistency. Data are collected through field visits to the hospitals and interviews withsubjects. The setting of the study includes all hospitals in Baghdad City which are (43) hospitals. Thesehospitals are distributed on three health directorates as; (8) for Medical City Directorate, (13) for Al-KarkhHealth Directorate, and (22) for Al-Rusafa Health Directorate. The sample is consisted of (43) nurse managerand (101) head nurse. It is purposive “non-probability” ones and it is selected with respect to the selectioncriteria of number of years in nursing and number of years in nursing management for no less than one year.Data of the study are analyzed through descriptive data analysis approach, cluster analysis and factoranalysis. The study reveals that variables that include age, gender, level of education, place of work, numberof years in nursing, number of years in nursing management, years of experience in electronic managementand the duration of each training session in nursing management have an impact in improving the quality ofnursing management. The findings indicate that electronic planning management plays more effective role in thefuture of the electronic management and the quality of operating nursing care. So far, we provide sufficientanswers to all questions and hypotheses that the present study has presented. The study recommends that thereis necessity to prepare and implement specialized programs which are concerned in electronic management forthe preparation of managerial leaders in this field. Being relied on electronic learning curriculum in general andspecifically electronic management in nursing courses with respect to what have been accomplished in developednations’ universities. Nursing staff have to be encouraged for enrollment in educational and training sessions asbeing relative to electronic management. Reporting, monitoring, evaluation and promotion for participants systemcan be initiated. National comprehensive studies that depend on comparison and targeted large number of healthorganizations in public and private sectors, and nursing staff for identification of barriers for the implementationand presentation of the recommendations, solutions, and the appropriate approaches that develop technical,managerial and leadership aspects. Concern can be presented with regard to training sessions in the field ofelectronic management, especially that of electronic planning management.